Experimental and Numerical Investigation on Shear Transfer of Concrete Specimens Strengthened with CFRP Sheets under Tensile Forces - Al-Hadithi, Abdullkader I.; Mahmood, Akram S.; Abdul-Hameed, Yasmin S. (Nahrain University College of Engineering Journal, 2017)
This study presents experimental and numerical investigations that concern the behavior of pull-off for normal and high strength concrete specimens strengthened with various configurations of carbon fiber reinforced polymer (CFRP) sheets. Three parameters have been investigated; the first is the strength of concrete by casting half of samples as normal strength concrete and the other as high strength concrete. The second parameter is the ratio of reinforcement crossing the shear plane. The third parameter is the CFRP strengthened. Three dimensional finite elements tools with eight-node elements are used to represent concrete, whereas embedded bar element type is used to represent the reinforcement. Nonlinear behavior of concrete in compression, tension and the reduction of the shear modulus due to cracking are be taken into account.A finite element which was used to representconcrete is three dimensional with eight nodeselements and embedded bar elements to represent the reinforcement. Nonlinear behavior of concrete in compression, tension and the reduction of the shear modulus due to cracking are be taken intoaccount.